How Elections Matter: Theory and Evidence from Environmental Policy - List John A.; Sturm Daniel (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2006)
This paper explores to what extent secondary policy issues are infuenced by electoral incentives. We develop a two dimensional political agency model in which a politician decides on both a frontline policy issue and a secondary policy issue. The model predicts when the incumbent should manipulate the secondary policy to attract voters. We test our model by using panel data on environmental policy choices in the U.S. states. In contrast to the popular view that secondary policies are largely determined by lobbying, we find strong effects of electoral incentives.
urn:nbn:de:bvb:19-epub-768-5
Keywords: D72; H72; Q58; 330; elections; environmental policy; lobbying; term limits